Human Capital as a Pushing Factor of Export: The Case of Four South Asian Economies - Bhavan, T. (Asian Development Policy Review, 2017)
This study investigates whether human capital serves as a pushing factor of exports of goods and services. Thus, this study takes four South Asian countries such as Bangladesh, India, Nepal, Pakistan and Sri Lanka into an account to test the relationship between human capital and export performance. The time series data that were extracted from the World Bank and the United Nations Development Program statistical databases, running from 1990 to 2015, used for data analysis. Following the Hausman test, the study employs Fixed Effect model to derive the results. The results suggest that human capital has a positive and significant effect on export performance in these countries, and lead to conclude that focusing on human capital development to enhance the export performance can be seen as one of the strategies to overcome trade deficit.